A Two-Stage Algorithm of Numerical Evaluation of Integrals in Number-Theoretic Methods (Journal of Computational Mathematics, 1999)
To improve the numerical evaluation of integrals in Number-Theoretic Methods, we give a two-stage algorithm. The main idea is that we distribute the points according to the variations of the quadrature on the subdomains to reduce errors. The simulations results are also given.